IMPLEMENTATION OF THE ‘BERKAT SAYANG’ PROGRAM FOR VULNERABLE GROUPS IN SIDOARJO REGENCY - Zalianty, Marcella Riski; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to determine how the Berkat Sayang Program implemented by the Sidoarjo Social Services Agency has addressed hunger among vulnerable groups in Sidoarjo Regency. Method:  A qualitative descriptive method was used, with data collected through interviews, observation, and documentation. Informants consisted of the Head of the Personnel Subdivision of the Sidoarjo Social Services Agency, Social Services Agency staff, catering parties, and elderly beneficiaries who were directly involved in the implementation of the program. Results: The results of the study show that the implementation of the Berkat Sayang Program is in accordance with Edward III's theoretical indicators and provides tangible benefits for the welfare of neglected elderly people. Communication has been clear through coordination and socialization meetings between the Social Services Agency and TKSK along with the beneficiaries. In terms of resources, this program is supported by cross-sector human resources and increasing APBD funding. The implementers showed high commitment with the innovation of a geotag application to increase the accuracy of aid delivery by catering providers, even though distribution was sometimes hampered by weather. The bureaucratic structure has been organized through SOPs and a digital reporting system so that implementation is systematic and accountable. However, bureaucratic obstacles arise when replacing the names of deceased beneficiaries, as it is necessary to wait for the Regent's Decree for the following fiscal year, thereby reducing bureaucratic flexibility. Novelty:  The novelty of this research lies in the specific application of George C. Edward III's implementation theory to examine the Berkat Sayang program in Sidoarjo, focusing on indicators of communication, resources, disposition, and bureaucratic structure in social policies for vulnerable groups.